2018
DOI: 10.1093/annonc/mdx753
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of upfront pathology review in the randomised PORTEC-3 trial for high-risk endometrial cancer

Abstract: BackgroundIn the PORTEC-3 trial, women with high-risk endometrial cancer (HR-EC) were randomised to receive pelvic radiotherapy (RT) with or without concurrent and adjuvant chemotherapy (two cycles of cisplatin 50 mg/m2 in weeks 1 and 4 of RT, followed by four cycles of carboplatin AUC5 and paclitaxel 175 mg/m2). Pathology review was required before patient enrolment. The aim of this analysis was to evaluate the role of central pathology review before randomisation.Patients and methodsA total of 1295 cases und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 25 publications
(19 reference statements)
2
49
0
Order By: Relevance
“…This emphasizes that the difference in recurrence and RFS is not driven by (preventable) vaginal recurrences, but that MMR status can identify patients who are at risk for clinically significant recurrences. Combining this with the previously reported randomized trials in a similar population that had high distant recurrence rates despite receiving aggressive adjuvant treatment, more effective therapy is urgently needed.…”
Section: Discussionmentioning
confidence: 88%
“…This emphasizes that the difference in recurrence and RFS is not driven by (preventable) vaginal recurrences, but that MMR status can identify patients who are at risk for clinically significant recurrences. Combining this with the previously reported randomized trials in a similar population that had high distant recurrence rates despite receiving aggressive adjuvant treatment, more effective therapy is urgently needed.…”
Section: Discussionmentioning
confidence: 88%
“…Levels of reproducibility of these tumour characteristics are similar to our results for LVSI assessment. None of the previous studies specifically focused on LVSI assessment, but there are two studies that report on reproducibility of LVSI in EC . LVSI and other tumour characteristics were reviewed as part of an upfront pathology review before randomisation in the PORTEC‐3 trial .…”
Section: Discussionmentioning
confidence: 99%
“…None of the previous studies specifically focused on LVSI assessment, but there are two studies that report on reproducibility of LVSI in EC . LVSI and other tumour characteristics were reviewed as part of an upfront pathology review before randomisation in the PORTEC‐3 trial . A high rate of interobserver agreement between the original pathology report and central pathology review was found for LVSI (κ = 0.72).…”
Section: Discussionmentioning
confidence: 99%
“…These microscopy‐based diagnoses are the current standard and serve as important input for (adjuvant) treatment decisions. However, considerable interobserver variation, in particular in high‐grade EC, is recognised, and centralised review prior to trial inclusion has pointed out that the therapeutic consequences are not negligible . This situation prompted research into the incorporation of robust diagnostic markers, which yields novel narrowly defined diagnostic entities.…”
Section: Introductionmentioning
confidence: 99%